Incorporation of bioactive compounds in fruit and vegetable products through osmotic dehydration: a review - Huerta-Vera, Karina; Flores-Andrade, Enrique; Contreras-Oliva, Adriana; Villegas-Monter, Ángel; Chavez-Franco, Sergio; Arévalo-Galarza, Ma. de Lourdes (Revista Mexicana de Ciencias Agrícolas, 2024)
The consumer is increasingly interested in their state of health and well-being, so the demand for functional foods has increased. The impregnation of bioactive compounds in fruit and vegetable products is a recent technology that opens a door of opportunity to a more demanding market, so a bibliographic review of the latest studies provides an overview for future work on the subject. The impregnation of bioactive compounds in the porous fraction of fruits and vegetables is achieved by osmotic dehydration (OD). In this sense, knowing the OD factors that determine the impregnation of bioactive compounds in plant tissues, their physicochemical stability during storage, and the latest trends in osmo-dehydrated fruit and vegetable products that could be considered functional foods is very important. Therefore, this review considered scientific information from different databases and was organized into three sections that are discussed: fundamentals of the OD, fruit and vegetable products enriched with bioactive compounds, and the physicochemical stability of these products during storage.
Keywords: dehydrated foods; food stability; functional foods; impregnation